Statistical Relationship Between the Decrease of Major Seismicity and Drought in Southern California Since 1900 - Bragato, Pier Luigi (Frontiers in Earth Science, 2021)
The seismicity in Southern California significantly decreased over the last decades. The decrease went in parallel with the reduction of meteoric groundwater recharge, which is a well-known factor capable of affecting seismicity. In this work the existence of a systematic statistical relationship was investigated statistically by comparing the time density of Mw≥5.7 earthquakes since 1900 with the time series of the Palmer Drought Severity Index (PDSI), an indicator of soil moisture roughly correlated with groundwater recharge. Given the non-stationarity of the two signals, the formal comparison was performed using both binomial logistic regression and cointegration testing. The analysis showed a significant statistical relationship, with peaks of seismicity eight years behind those of PDSI. This finding suggests the hypothesis that groundwater recharge might affect earthquakes at a multi-year time scale. Proving this theory requires accurate measures and hydrogeological modeling, which is behind the scope of this work. Nonetheless, according to previous studies, the observed time lag might be explained by the slow propagation of pore pressure from the surface to the seismogenic volume. The ongoing trend towards an arid climate, made more evident by the recent severe droughts, might have contributed to the earthquake reduction of the last decades. The connection is particularly evident in the Salton Trough, with possible implications for the interpretation of its paleoseismicity.